Customer acceptance toward Islamic personal fnancing in Pakistan - Muhammad, Ali; Syed Ali, Raza; Puah, Chin Hong; Muhammad Shujaat, Mubarik (Springer Nature, 2023)
The present study is the frst attempt in Pakistan to examine the determinants of Islamic personal fnancing by using a modifed theory of reasoned action (TRA) model. This study uses the two primary constructs of the TRA model: subjective norm and attitude. Additionally, this study modifed this model by introducing three relevant factors: pricing of Islamic personal fnancing, a religious obligation, and government support to predict the intention of Islamic bank customers about Islamic personal fnancing. Sample data were conveniently drawn from the Islamic bank customers with the help of a self-administered survey-based questionnaire. The study sample comprised 484 responses of full-fedged Islamic bank customers located in the biggest city of Pakistan. Out of 484 responses, this study considered 471 responses and ignored 13 responses due to incomplete information provided by the customers. The data was statistically analyzed by employing Structural equation modeling SEM. Overall, the study results suggest that pricing of Islamic personal fnancing and religious obligation has a negative and signifcant impact on the intention to use Islamic personal fnancing; however, attitude and social infuence were found to be positive but insignifcant predictors. In addition, government support is positive and signifcantly associated with using Islamic personal fnancing. This study has some practical implications for Islamic bank managers and the government of Pakistan. Furthermore, Islamic banks should capture the need for Islamic personal fnancing, while government support may help promote this service for Islamic banks in Pakistan.